Mystical and Mythological Explanatory Works of Assyrian and Babylonian Scholars - Livingstone, Alasdair (1986)
mit Autographien von BM 47860, K 4245 + 17990, BM 47463 = 81-11-3,168, BM 41361444179 = 81-4-28,910 + 81-7-1, 1940, BM 37055, K 7979.